Joseph Conrad. Corazón de las tinieblas. Translated, introduced and annotated by Jorge Fondebrider. Ciudad Autónoma de Buenos Aires : Eterna Cadencia, 2021. 240 pp. ISBN 978-987-712-222-0 - Fernández, Silvana Noelí (Joseph Conrad today.)
Reseña de Joseph Conrad. Corazón de las tinieblas. Translated, introduced and annotated by Jorge Fondebrider. Ciudad Autónoma de Buenos Aires: Eterna Cadencia, 2021. 240 pp. ISBN 978-987-712-222-0.